Outcomes After Operative and Nonoperative Treatment of Proximal Hamstring Avulsions: A Systematic Review and Meta-analysis. Issue 11 (September 2018) - Bodendorfer, Blake M.; Curley, Andrew J.; Kotler, Joshua A.; Ryan, James M.; Jejurikar, Neha S.; Kumar, Anagha; Postma, William F.
Background: No meta-analysis has compared outcomes of operative and nonoperative proximal hamstring avulsion treatment. Purpose: To compare outcomes of operative and nonoperative proximal hamstring avulsion treatment, including acute, chronic, partial, and complete repairs. Study Design: Meta-analysis. Methods: PubMed, CINAHL, SPORTdiscus, Cochrane Library, EMBASE, and Web of Science were searched up to July 2016. Three authors screened the studies and performed quality assessment using criteria from the Methodologic Index for Nonrandomized Studies. A best evidence synthesis was subsequently used. Results: Twenty-four studies (795 proximal hamstring avulsions) were included. Twenty-two studies included proximal hamstring avulsion repairs; 1 study had proximal hamstring avulsion repairs and a control group of nonoperatively treated proximal hamstring avulsions; and 1 study had solely nonoperatively treated proximal hamstring avulsions. The majority of studies were of low methodological quality. Overall, repairs had significantly higher patient satisfaction (90.81% vs 52.94%), hamstring strength (85.01% vs 63.95%), Lower Extremity Functional Scale scores (72.77 vs 69.53), and single-legged hop test results (119.1 vs 56.62 cm) (all P < .001); complications occurred in 23.17% of cases. Compared with chronic repairs, acute avulsion repairs had greater patient satisfaction (95.48% vs 83.79%), less pain (1.07 vs 3.71), and greater strength (85.2% vs 82.8%), as well as better scores for the Lower Extremity Functional Scale (75.64 vs 71.5), UCLA activity scale (University of California, Los Angeles; 8.57 vs 8.10), and Single Assessment Numeric Evaluation (93.36 vs 86.50) (all P < .001). Compared with partial avulsion repairs, complete avulsion repairs had higher patient satisfaction (89.64% vs 81.35%, P < .001), less pain (1.87 vs 4.60, P < .001), and higher return to sport or preinjury activity level, but this was insignificant (81.43% vs 73.83%, P = .082). Partial avulsion repairs had better hamstring strength (86.04% vs 83.71%, P < .001) and endurance (107.13% vs 100.17%, P < .001). Complete repairs had significantly higher complication rates (29.38% vs 11.27%, P = .001). Conclusion: Proximal hamstring avulsion repair resulted in superior outcomes as compared with nonoperative treatment, although the complication rate was 23.17%. The nonoperative group was quite small, making a true comparison difficult. Acute repairs have better outcomes than do chronic repairs. Complete avulsion repairs had higher patient satisfaction, less pain, and a higher complication rate than partial avulsion repairs, although partial avulsion repairs had better hamstring strength and endurance. Studies of high methodological quality are lacking in terms of investigating the outcomes of proximal hamstring avulsion repairs.